Penetapan Nilai Sun Protection Factor (SPF) pada Destilat Rimpang Jahe Emprit (Zingiber officinale var. Amarum) dengan Metode Spektrofotometri UV-Vis - Talia, Nadia Debi; Risando, Khoirum Salsa Billa; Qurohman, Rajib Fadh; Khumayyah, Fadillah Nur; Putri, Sahara Nadia; Rossania, Nadya; Purwanto, Diyan Sakti (Pusat Riset dan Inovasi Nasional, 2025)
Emprit ginger (Zingber officinale var Amarum) is one of the local ginger varieties in Indonesia that has great potential in the pharmaceutical and cosmetic fields because of the content of active compounds in it, especially phenolic and flavonoid compounds. These compounds are often known to have high antioxidant activity so that they are able to ward off free radicals, and act as compounds that are able to protect the skin from exposure to UV rays. One of the potentials of these compounds is as an active ingredient in sunscreen preparations. Sunscreen compounds are compounds that absorb, reflect, or spread ultraviolet (UV) rays from the sun, so that they can cause skin damage such as premature aging, burns, and skin cancer. This research aims to evaluate the activity of sunscreen from emprit ginger distillate based on the Sun Protection Factor (SPF) value. Emprit ginger distillate (Zingber officinale var Amarum) is obtained through the process of water distillation using aquadest as a solvent, then its activity is tested in vitro using the UV spectrophotometry method at a wavelength of 290–320 nm with an interval of every 5 nm. Test results show that the SPF value of ginger distillate emprit on three consecutive replications is 26,72; 36,12; and 31,69. These three values are included in the ultra protection category because they have an SPF value of ≥ 15. Based on these results, it can be concluded that emprit ginger distillate has a very good potential as a natural active ingredient in the formulation of natural sunscreen preparations.